A Spirituality of Liberation: The Rosary as a Means of Cultivating Simone Weil’s Attention - Faiz Abimanyu Wiguna; Ikhaputri Widiantini (Jurnal Ledalero, 2026)
This paper explores the interpretation of the Rosary through the philosophical thoughts of Simone Weil, highlighting its potential as a means of cultivating Weil’s living philosophy of “attention,” and by so presenting a spirituality of liberation that attempts to present in whole the twofold image of Weil as both a mystic and a radical. Through Weil’s theory of attention and her two-step philosophical method, which involves reflection on several personal experiences formed through the Rosary, this paper presents a practical formulation of Weil’s moral and religious teaching on attention, especially highlighting the potential for a spirituality of liberation —contributing to the progressive discourse in the philosophy of religion within the Roman Catholic tradition.